The Effect of Work Environment and Work Motivation on Employee Performance at Balitbangda Office of Donggala Regency - Warzukni, Ikna; Idris; Kornelius, Yoberth; Ega Nugraha, Mohammad (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of work environment and work motivation on employee performance at the Regional Research and Development Agency (Balitbangda) of Donggala Regency. Using a quantitative causal approach with saturated sampling, data were collected from 40 employees and analyzed using multiple linear regression. The results show that the work environment has a positive but insignificant effect, while work motivation has a positive and significant effect on performance. Simultaneously, both variables significantly influence employee performance (R² = 0.826). These findings imply that strengthening employee motivation is more critical than improving the work environment in enhancing performance.